Aktivitas Antimikroba Biji Teratai (Nymphaea pubescens L.) Terhadap Bakteri Aeromonas hydrophila, Streptococcus agalactiae dan Jamur Saprolegnia sp. - Dewi Roma Widya; Dwi Suryanto; Desrita Desrita (AQUACOASTMARINE, 2014)
Disease prevention in fish using chemicals or antibiotics leads to microbial resistance. One alternative to control the fish disease is to use plant extract. The aim of this study was to investigate the antimicrobial activity of lotus seeds (Nymphaea pubescens L.) on pathogenic bacteria and fungi in fish. The lotus seed was extracted with several solvent, such as n-hexsane, ethyl-acetate, and methanol. Antimicrobial activity assay was carried out using disc diffusion method. Phytochemical preliminary test was done to determine seed chemical compounds. The brine shrimp lethality test was utilised to determine the extract toxicity. The result showed that all extracts inhibited Aeromonas hydrophila, Streptococcus agalactiae, and Saprolegnia sp. growth to some extent. The extract was to inhibit more to S. agalactiae with inhibition zone of 10.72 mm. In general extract of n-heksana was to inhibit more to the test microbes. Cytotoxic activity (LC50) was <1000 μg/ml. Preliminary test of phytochemical compound showed that extracts of lotus seed contains alkaloid, fenolic, glicoside, saponin and steroid/terpenoid.Keywords: Antimicrobial activity, microbial pathogenic, Nymphaea pubescens L.